Toll-Like Receptors and Dental Mesenchymal Stromal Cells - Andrukhov, Oleh (Frontiers in Oral Health, 2021)
Dental mesenchymal stromal cells (MSCs) are a promising tool for clinical application in and beyond dentistry. These cells possess multilineage differentiation potential and immunomodulatory properties. Due to their localization in the oral cavity, these cells could sometimes be exposed to different bacteria and viruses. Dental MSCs express various Toll-like receptors (TLRs), and therefore, they can recognize different microorganisms. The engagement of TLRs in dental MSCs by various ligands might change their properties and function. The differentiation capacity of dental MSCs might be either inhibited or enhanced by TLRs ligands depending on their nature and concentrations. Activation of TLR signaling in dental MSCs induces the production of proinflammatory mediators. Additionally, TLR ligands alter the immunomodulatory ability of dental MSCs, but this aspect is still poorly explored. Understanding the role of TLR signaling in dental MSCs physiology is essential to assess their role in oral homeostasis, inflammatory diseases, and tissue regeneration.